Development Of The Three Tier Diagnostic Test Based 'Higher Order Thinking Skills' Instrument - Sari, Ni Wayan Novita; Sunyono, Sunyono (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study developed a knowledge assessment instrument of three tier diagnostic tests based on higher order thinking skills (HOTS) which aims to diagnose students' understanding in higher-order thinking and reduce misconceptions. The research method uses ADDIE (Analysis-Design-Develop-Implement-Evaluate) and the subject is class VII junior high school students with 2017 odd semester curriculum materials. This study used HOTS-based knowledge assessment instruments of three tier diagnostic tests of 20 items. The results of the instrument expert validation test based on aspects of content, construct, and language assessment have an average score of 90, 88, and 89 with a proper assessment. The data were analyzed using rasch model and the item reliability index was 0.89, the reliability index of the respondents was 0.91, and Cronbach's alpha value was 0.93, which meant the reliability of the questions obtained was good. The results of the students 'answer patterns are six criteria: understanding concepts, misconceptions (+), misconceptions (-), misconceptions, guessing / lack of confidence / luck, and not understanding the concepts used to diagnose learners' understanding in measuring high-level thinking skills (HOTS) which is integrated with the dimensions of factual, conceptual and procedural knowledge. Misconceptions that occur in students have three criteria, namely misconception (+), misconception (-), and misconception, and the most experienced by students is a misconception (-) in the C4 cognitive level which is integrated with the conceptual knowledge dimension on the substance characteristic material . This misconception (-) can be reduced through the correct concept with the right reasons.